Adhesive Behavior of Propolis on Different Substrates - Saccardi, Leonie; Schiebl, Jonas; Weber, Katharina; Schwarz, Oliver; Gorb, Stanislav; Kovalev, Alexander (Frontiers in Mechanical Engineering, 2021)
Propolis is a sticky substance used by bees to seal their hive and protect the colony against pathogens. Its main components are plant resins, beeswax, essential oils, pollen, and other organic substances. The chemical and medicinal properties of propolis have been extensively studied, but little is known about its physical and especially adhesive properties. To gain a better understanding of propolis and its potential for adhesive applications, we performed several experiments, including adhesion tests with propolis in different conditions and on various substrates, differential scanning calorimetry analysis, and compression tests. Propolis shows clear viscoelastic behavior and temperature-dependent mechanical properties. Our results demonstrate that propolis adheres well to a wide range of substrates from glass to PTFE, but also enables stronger adhesion at higher temperatures and longer contact times. Even underwater, in wet conditions, quite a substantial adhesion was measured. The data are interpreted from a biomechanical point of view, and the significance of the obtained results for bee biology is discussed.